2005
DOI: 10.1590/s0100-69162005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Uso do cilindro infiltrômetro único em diferentes solos

Abstract: O infiltrômetro de anéis concêntricos (IAC) tem sido empregado para a determinação da velocidade de infiltração básica de água no solo (VIB), porém, para sistemas de irrigação por aspersão, a melhor técnica é a que apresenta carga hidráulica zero, como nos simuladores de chuva. O presente trabalho teve o objetivo de avaliar o uso de infiltrômetro de cilindro único (ICU), comparando-o com o IAC e com um simulador de chuva. O experimento foi realizado em dois tipos de solo classificados como Latossolo Vermelho d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
(2 reference statements)
0
3
1
4
Order By: Relevance
“…According to the Tukey test at 0.05 probability level, there was no significant difference between the two curves (Table 5). These results do not agree with those obtained by Simões et al (2005), who studied T ie in Cambisols with hydraulic head of 5 cm and observed infiltration rates of 10.44 and 14.43 cm h -1 , respectively, for the same type of soil. The no-tillage system, considered as a conservation practice, promotes profound changes in the relations between soil, water and plant, improving soil physical and chemical attributes and contributing to the improvement of porosity, soil density and, consequently, water infiltration (Klein & Libardi, 2002).…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…According to the Tukey test at 0.05 probability level, there was no significant difference between the two curves (Table 5). These results do not agree with those obtained by Simões et al (2005), who studied T ie in Cambisols with hydraulic head of 5 cm and observed infiltration rates of 10.44 and 14.43 cm h -1 , respectively, for the same type of soil. The no-tillage system, considered as a conservation practice, promotes profound changes in the relations between soil, water and plant, improving soil physical and chemical attributes and contributing to the improvement of porosity, soil density and, consequently, water infiltration (Klein & Libardi, 2002).…”
Section: Resultscontrasting
confidence: 92%
“…In addition, the curves showed a similar behavior throughout the experiment ( Figure 1C); during the initial time, the infiltration rate was higher, but during the rest of the test, there was almost no difference between the curves. Simões et al (2005) -1 for Cambisols using the model (IAC), with hydraulic heads of 5 and 10 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Simões et al (2005), em estudos em um cambissolo, encontraram valores da taxa de infiltração estável, com uso de simulador de chuvas, de 57,7 mm h -1 -valores próximos aos encontrados neste trabalho. a mesma tendência apresentada entre as taxas de infiltração, com diferentes perfis de precipitação pluvial, sugere que, em condições de superfície do solo bem protegida contra o impacto direto das gotas de chuva, o perfil de precipitação pluvial não influencia a taxa de infiltração, sendo ele influenciado somente pelas precipitações pluviais sucessivas, ou seja, pela lâmina total aplicada.…”
Section: Resultsunclassified
“…Diversos métodos podem ser utilizados para a determinação da velocidade de infiltração da água no solo, dentre os quais se destacam os simuladores de chuva e os infiltrômetros de anéis concêntricos (IAC). Os IAC são mais utilizados devido à sua facilidade de manejo e ao baixo custo de aquisição, quando comparados aos simuladores de chuva (COELHO et al, 2000;SIMÕES et al, 2005). Além disso, os IAC podem ser utilizados em locais em que o acesso à água é restrito, uma vez que a quantidade utilizada nos ensaios é relativamente pequena, quando comparada à necessária para a realização de um ensaio com simulador de chuvas.…”
Section: Introdução E Fundamentação Teóricaunclassified